2019
DOI: 10.1002/lary.27726
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Disease Severity and Microbiome in Chronic Rhinosinusitis

Abstract: Objective The role of the microbiome in the etiology of chronic rhinosinusitis (CRS) is still in debate. Reductions in richness and diversity have been implicated in CRS; however, limited knowledge exists regarding the impact of the severity of disease on the microbiome. The associations between constituents of the microbiome and the degree of mucosal inflammation and tissue eosinophilia are described. Methods A cross‐sectional study of CRS and non‐CRS patients who underwent endoscopic sinus surgery was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
4
20
0
1
Order By: Relevance
“…(Copeland et al 2018) reported that Shannon diversity was significantly increased in CRSsNP patients compared to that in control and CRSwNP patients. Moreover, a number of previous studies(Biswas et al 2017; Hoggard et al 2017; Chalermwatanachai et al 2018; Gan et al 2019; Rom et al 2019) indicated that alpha diversity was increased, decreased, or unchanged in CRS compared to that in control, and this was dependent upon the alpha diversity index.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(Copeland et al 2018) reported that Shannon diversity was significantly increased in CRSsNP patients compared to that in control and CRSwNP patients. Moreover, a number of previous studies(Biswas et al 2017; Hoggard et al 2017; Chalermwatanachai et al 2018; Gan et al 2019; Rom et al 2019) indicated that alpha diversity was increased, decreased, or unchanged in CRS compared to that in control, and this was dependent upon the alpha diversity index.…”
Section: Discussionmentioning
confidence: 94%
“…For the medical treatment of CRS, antibiotics such as penicillins/betalactams and macrolides were prescribed in about 70% of CRS visits(Smith et al 2013). However, most of previous metagenomic analyses(Aurora et al 2013; Choi et al 2014; Biswas et al 2015; Ramakrishnan et al 2015; Biswas et al 2017; Cope et al 2017; Hoggard et al 2017; Jain et al 2017; Lal et al 2017; Ramakrishnan et al 2017; Chalermwatanachai et al 2018; Copeland et al 2018; Koeller et al 2018; Mahdavinia et al 2018; Biswas et al 2019; Gan et al 2019; Paramasivan et al 2019; Rom et al 2019) examining CRS excluded patients who had taken antibiotics within approximately one month prior to sampling. Here, we performed metagenomics and proteomics analyses using nasal secretions in healthy control and CRS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10-20 years, the incidence of myocarditis and pericarditis has increased significantly [18]. Non-coronarogenic myocardial diseases account for 7-9% of all diseases of the cardiovascular system [10,21]. It has been proven that there is a direct connection between influenza and acute respiratory infections with subsequently developing chronic therapeutic pathology and serious somatic complications [22].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the AR patients' bNM was less rich in terms of residential bacteria and associated with a reduced bacterial phylogenetic diversity compared to the HS group. Interestingly, reduced diversity in the bNM was identi ed also in other respiratory diseases such as in patients with Chronic Rhinosinusitis (CRS) [56,57], in patients with asthma [58], and in patients affected by granulomatosis with polyangiitis [59]. The importance of a diverse microbiota has been widely documented as pivotal in maintaining the mucosa integrity and an effective immune system [16,45,60].…”
Section: Discussionmentioning
confidence: 99%